Kinerja Usaha Mikro, Kecil Dan Menengah (UMKM) Pada Saat Covid-19 Di Jawa Timur - Yenny Kornitasari; Dita Nurul Aini Mustika Dewi (Oikonomia: Jurnal Manajemen, 2023)
Purpose The COVID-19 pandemic has shaken the social and economic conditions of society at both the global and national levels. As a sector that is the backbone of the East Java economy, the micro, small and medium enterprises (MSMEs) sector has also been affected by this crisis. Therefore, this study aims to analyze the performance of micro, small and medium enterprises during the COVID-19 pandemic in East Java. Methodology The method used in this study is descriptive quantitative analysis to show in real terms the data and phenomena in the field that are presented based on a survey. Findings he results of this study explain that the COVID-19 pandemic has had a serious impact on the business world, especially for Micro, Small and Medium Enterprises (MSMEs) in East Java. The performance of Micro, Small and Medium Enterprises (MSMEs) experienced losses and also had difficulty obtaining raw materials due to the restriction policy. In addition, restrictions on people's mobility have an impact on sales, requiring a new marketing strategy. Suggestion Most of Ultra Micro and Micro in East Java do not have extensive knowledge about online marketing. Capital assistance, access to raw materials as well as marketing assistance will be very helpful for ultra-micro and micro businesses in facing future challenges.